Long-term mortality and causes of death associated with Staphylococcus aureus bacteremia. A matched cohort study. Issue 4 (October 2016) - Gotland, N.; Uhre, M.L.; Mejer, N.; Skov, R.; Petersen, A.; Larsen, A.R.; Benfield, T.; ,
Summary: Objectives: Data describing long-term mortality in patients with Staphylococcus aureus bacteremia (SAB) is scarce. This study investigated risk factors, causes of death and temporal trends in long-term mortality associated with SAB. Methods: Nationwide population-based matched cohort study. Mortality rates and ratios for 25, 855 cases and 258, 547 controls were analyzed by Poisson regression. Hazard ratio of death was computed by Cox proportional hazards regression analysis. Results: The majority of deaths occurred within the first year of SAB (44.6%) and a further 15% occurred within the following 2–5 years. The mortality rate was 14-fold higher in the first year after SAB and 4.5-fold higher overall for cases compared to controls. Increasing age, comorbidity and hospital contact within 90 days of SAB was associated with an increased risk of death. The overall relative risk of death decreased gradually by 38% from 1992–1995 to 2012–2014. Compared to controls, SAB patients were more likely to die from congenital malformation, musculoskeletal/skin disease, digestive system disease, genitourinary disease, infectious disease, endocrine disease, injury and cancer and less likely to die from respiratory disease, nervous system disease, unknown causes, psychiatric disorders, cardiovascular disease and senility. Over time, rates of death decreased or were stable for all disease categories except for musculoskeletal and skin disease where a trend towards an increase was seen. Conclusion: Long-term mortality after SAB was high but decreased over time. SAB cases were more likely to die of eight specific causes of death and less likely to die of five other causes of death compared to controls. Causes of death decreased for most disease categories. Risk factors associated with long-term mortality were similar to those found for short-term mortality. To improve long-term survival after SAB, patients should be screened for comorbidity associated with SAB.